Diverse radiotherapy fractionation in malignant melanoma: a case report - Shen, Jiayi; Ge, Yizhi; Zhang, Puchang; Gao, Han; Wang, Lijun (Frontiers in Oncology, 2025)
Malignant melanoma (MM) is a highly aggressive tumor, with a median overall survival (mOS) of only 8 to 12 months for its metastatic form. However, studies focusing on the efficacy of different radiotherapy (RT) fractionation regimens for MM are limited. Here, we report the case of a 60-year-old male who presented with a one-month history of intermittent abdominal pain and was subsequently diagnosed with MM. Following disease progression on systemic therapy, the patient was treated with different fractionation regimens, including 5 Gy per fraction and 3 Gy per fraction. After the failure of immunotherapy, RT effectively controlled the tumor burden. Notably, the patient received different doses of RT and achieved different outcomes. This case report demonstrates that RT could serve as a viable option for patients who have developed resistance to immunotherapy and low-dose RT may enhance tumor immune response when combined with immunotherapy.